2016
DOI: 10.1002/anie.201604478
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Interfacial Doping of Organic Small Molecules for High Performance n‐type Thermoelectric Materials

Abstract: Development of chemically doped high performance n-type organic thermoelectric (TE) materials is of vital importance for flexible power generating applications. For the first time, bismuth (Bi) n-type chemical doping of organic semiconductors is described, enabling high performance TE materials. The Bi interfacial doping of thiophene-diketopyrrolopyrrole-based quinoidal (TDPPQ) molecules endows the film with a balanced electrical conductivity of 3.3 S cm(-1) and a Seebeck coefficient of 585 μV K(-1) . The newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…[2] To maximize the energy conversion efficiency, both high-performance complementary p-type and n-type legs are required. [3] Compared to the p-type polymers with high conductivity over 1000 Scm À1 and power factors (PF ¼ sS 2 )o fu pt o 100 mWm À1 K À2 , [4] only af ew n-type polymers exhibit conductivities over 1Scm À1 and power factors over 1 mWm À1 K À2 . [5] In addition, most n-type polymer thermo-electric materials showed inferior stability under ambient conditions,f urther limiting their applications.…”
mentioning
confidence: 99%
“…[2] To maximize the energy conversion efficiency, both high-performance complementary p-type and n-type legs are required. [3] Compared to the p-type polymers with high conductivity over 1000 Scm À1 and power factors (PF ¼ sS 2 )o fu pt o 100 mWm À1 K À2 , [4] only af ew n-type polymers exhibit conductivities over 1Scm À1 and power factors over 1 mWm À1 K À2 . [5] In addition, most n-type polymer thermo-electric materials showed inferior stability under ambient conditions,f urther limiting their applications.…”
mentioning
confidence: 99%
“…Recently, important progress was made on n‐type thermoelectric polymers. It was reported that n‐type conductive polymers containing metal elements can have good stability even under ambient conditions . Zhu et al synthesized and characterized poly(nickel‐ethylenetetrathiolate).…”
Section: Intrinsically Conductive Polymers For Thermoelectric Conversionmentioning
confidence: 99%
“…Chabinyc et al reported vapor‐doping PBTTT with F 4 TCNQ, and obtained a σ of 670 S cm −1 and a S of 42 µV K −1 , which lead to a large PF of 120 µW K −2 m −1 22. Inspired by the fact that the performance of n‐type OTEs is much lagging behind the p‐type counterparts, in recent years researchers have paid intensive attention to investigating OTEs based on n‐type semiconductors 6,23–25. Typical examples include N‐DMBI‐doped N2200, which has a σ of 8 × 10 −3 S cm −1 , a S of 850 µV K −1 , and a resulting PF of 0.6 µW K −2 m −1 15.…”
mentioning
confidence: 99%
“…Recently Pei et al reported the usage of BDPPV for thermoelectric applications by doping with N‐DMBI, which exhibited a σ of 14 S cm −1 and PF up to 28 µW K −2 m −1 25. Zhu and his colleagues have spent a lot of efforts on developing n‐type thermoelectric materials,23,24,26 and they have reported, by far, the highest PF values of organic thermoelectric materials, namely the N‐DMBI‐doped small molecule Q‐DCM‐DPPTT, which has a σ of 4–5 S cm −1 , a S of 660 µV K −1 and a PF of over 200 µW K −2 m −1 .…”
mentioning
confidence: 99%